2014
DOI: 10.1155/2014/758765
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Binary Organogels via Some Azobenzene Amino Derivatives and Different Fatty Acids: Self-Assembly and Nanostructures

Abstract: In present work the gelation behaviors of binary organogels composed of azobenzene amino derivatives and fatty acids with different alkyl chains in various organic solvents were designed and investigated. Their gelation behaviors in 20 solvents were tested as new binary organic gelators. It showed that the length of alkyl substituent chains and azobenzene segment have played a crucial role in the gelation behavior of all gelator mixtures in various organic solvents. Longer alkyl chains in molecular skeletons i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Rational assembly modes in organogels were proposed and discussed. In another continuous work, the gelation behaviors of binary organogels composed of azobenzene amino derivatives and fatty acids with different alkyl chains in various organic solvents were designed and investigated [52]. Their gelation behaviors in 20 solvents were tested as new binary organic gelators.…”
Section: Advances In Colloid Sciencementioning
confidence: 99%
“…Rational assembly modes in organogels were proposed and discussed. In another continuous work, the gelation behaviors of binary organogels composed of azobenzene amino derivatives and fatty acids with different alkyl chains in various organic solvents were designed and investigated [52]. Their gelation behaviors in 20 solvents were tested as new binary organic gelators.…”
Section: Advances In Colloid Sciencementioning
confidence: 99%
“…In another continuous work, the gelation behaviors of binary organogels composed of azobenzene amino derivatives and fatty acids with different alkyl chains in various organic solvents were designed and investigated [66]. The experimental results indicated that their gelation behaviors solvents can be regulated by changing the length of alkyl substituent chains and azobenzene segment.…”
Section: Nanomaterials -Toxicity and Risk Assessmentmentioning
confidence: 99%